Internalisasi Nilai-nilai Kegamaan pada Mahasiswa Prodi Pendidikan Bahasa Indonesia, FKIP, Universitas Madura dalam Beropini di Media Sosial - Laili Amalia; Yuliarsih Yuliarsih; Rohmah Indahwati; Mohammad Rudiyanto (KOLONI, 2022)
Technological advances have had a significant impact on society. Internet is one type of technology used to communicate. The fact that social media is used on the Internet is one of its benefits. The use of social media is growing rapidly nowadays. Social media can be utilized to increase knowledge if handled properly and effectively. Students are given the option to choose the information that best suits their needs. Also, it might help to become more proficient at making comments and sharing ideas on social media. This study uses a qualitative methodology by using sentences from the results of the Student Questionnaire of the Indonesian Language Education Study Program, FKIP Madura University as data and sources of research data. Techniques for collecting data through surveys and analyzing them qualitatively. When students share views on social media while maintaining their belief in Religious values. Aspects of faith, morals, and worship are one of the teachings of religion that must be instilled in humans. Through the educational process and teaching materials, students of the Indonesian Language Education Study Program, FKIP Madura University, are able to bring up aqidah and ethics. Religious principles are formally communicated through the integration and educational process. Views and behavior of other individuals that have been used in the use of social media by students. FKIP Madura University seeks to help students internalize religious values. So that the value of religious life can be expressed in the attitudes and behavior of students Keywords: religious values ​​and social media